Digitalization Process in Islamic Business: Literature Review - Anam, Moh. Khoirul; Masuwd, Mowafg Abrahem (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
Digitalization has become an essential component for modern businesses, and without it, companies struggle to keep pace in the era of Industry 4.0. However, there is still limited research on the impact of digitalization within Islamic or Sharia-compliant businesses. This study aims to explore digitalization in Islamic business, focusing specifically on Indonesia. The research employs a narrative review methodology, analyzing existing literature on Islamic business to provide a comprehensive overview of the importance of digitalization. The findings reveal that digitalization offers numerous advantages for businesses, including those in the Islamic sector. Islamic banks, as a key component of Islamic business, were among the first to embrace digitalization. The study also highlights that stakeholder support in Indonesia for the digitalization of Islamic businesses is sufficiently robust. This research provides a unique perspective on the evolution of digitalization in Islamic enterprises and is intended to encourage further studies in the field of Islamic business in the context of Industry 4.0.